Central Retinal Vein Occlusion in Hepatocellular Carcinoma - Tong Koh Yan; Sanjay Srinivasan (Journal of Ophthalmic Science, 2015)
A 66 year old Chinese male with a medical history of hypertension, diabetes mellitus and hepatitis B carrier was diagnosed with hepatocellular carcinoma in 2009. He underwent treatment with selective internal radiation spheres and sorafenib, and multiple cycles of chemotherapeutic agents such as bevacizumab, erlotinib, OXAFI ( intravenous oxaliplatin and doxorubicin given on days 1, 8 and 15 in a 28-day cycle, a daily continuous infusion of fluorouracil and subcutaneous interferon alfa-2b 5 million units administered thrice weekly), thalidomide, capecitabine, and rapamycin over the course of four years. Along the course of treatment, he developed pulmonary embolism and was initially started on anti-coagulation. Two months later, he developed hemoptysis and the anti-coagulants were stopped. During his routine ophthalmology visit for diabetic eye evaluation, he complained of blurring of vision of his left eye for the past four to five weeks. He was found to have central retinal vein occlusion (CRVO) of the left eye, associated with macular edema. Visual acuity was 6/15 for the right eye and 6/60 for the left eye. Eyelids, conjunctiva, cornea, anterior chamber, pupils, lens and ocular motility were normal. Humphrey visual field testing showed a superior arcuate and basal defect. This is the first reported case of CRVO in hepatocellular carcinoma. The etiology of CRVO is multifactorial, withhepatic malignancy, previous major surgery, multiple cycles of chemotherapy and cessation of anticoagulant therapyas possible aetiological factors. His background medical problems of diabetes and hypertension are further contributors.
Keywords: Occlusion